ANALISIS TINGKAT KEUNTUNGAN USAHA PENGGEMUKAN SAPI POTONG RAKYAT DI KABUPATEN WONOGIRI - Deasy Happyana (JURNAL ILMIAH PETERNAKAN TERPADU, 2017)
Beef cattle breeding business in Wonogiri District is dominated by small scale in which capital and profits too low. The size of the profits derived from the balance of the sale value of production and production costs that is issued by the breeder. The maximum profit would be achieved if all factors of production have been allocated in an optimal and efficient use, both technically and economically efficient manner. Objective analysis profit function is to describe the situation now, the circumstances in the future or planning and action of a business related to the rate of business profit and net income scale beef cattle farms of the people.The results showed that total revenue (TR) of beef cattle breeding business people have an average of Rp.89.360.625.00 per farmer per one period of fattening cattle, while the total cost (TC) on average Rp.85.119.873.00 each farmers per one period of fattening cattle. So that the magnitude of the rate of profit(π) obtained by each farmer in one period of fattening cattle for Rp.4.240.752.00 and the R / C ratio of 1:05. The results of the analysis showed that the profit rate of beef cattle breeding business in Wonogiri Regency financially advantageous (value profit π>  0 and the return value cost ratio of R / C> 1). Results of regression equation analysis function simultaneously benefit breeders show concentrate feed costs, labor costs and costs of cows significant ((P <0.05)) on the level of business profit beef cattle farms in Wonogiri. Based on the calculation of the value of R2 adjusted Rvalues obtained2  83.2% showed variable variation concentrate feed and forage costs, drug costs, labor costs, fees and charges cage feeder cattle can be explained by either a variable rate of the business profits of beef cattle breeders. The remaining 16.8% operating income level variable cattle ranchers explained by variations in other variables outside the model. Partially variable concentrate feed costs, labor costs and the cost of feeder cattle significantly (P <0.05) to the level of business profit breeding beef cattle people. As for the cost of forage ariable drug costs are not significant (P> 0.5) on the level of beef cattle breeding business benefit of the people. Keywords: Function Gain, Beef Cattle, Wonogiri